Two-dimensional electronic spectroscopy of the Qx to Qy relaxation of chlorophylls a in photosystem II core complex - Do, Thanh Nhut (2022)
Using two-dimensional electronic spectroscopy, we measured the Qx to Qy transfer dynamics of the chlorophyll a (Chl a) manifold in the photosystem II (PSII) monomeric core complex from Arabidopsis thaliana. A PSII monomeric core consists of 35 Chls a and no Chl b, thus allowing for a clear window to study Chl a Qx dynamics in a large pigment-protein complex. Initial excitation in the Qx band results in a transfer to the Qy band in less than 60 fs. Upon the ultrafast transfer, regardless of the excitation frequency within the Qx band, the quasi-transient absorption spectra are very similar. This observation indicates that Chl a's Qx to Qy transfer is not frequency selective. Using a simple model, we determined that this is not due to the lifetime broadening of the ultrafast transfer but predominantly due to a lack of correlation between the PSII core complex's Chl a Qx and Qy bands. We suggest the origin to be the intrinsic loss of correlation during the Qx to Qy internal conversion as observed in previous studies of molecular Chl a dissolved in solvents.